2016
DOI: 10.1039/c5mb00692a
|View full text |Cite
|
Sign up to set email alerts
|

New oligonucleotide derivatives as unreactive substrate analogues and potential inhibitors of human apurinic/apyrimidinic endonuclease APE1

Abstract: Human apurinic/apyrimidinic endonuclease APE1 is one of the key enzymes of the base excision DNA repair system. The main biological function of APE1 is the hydrolysis of the phosphodiester bond on the 5'-side of an apurinic/apyrimidinic site (AP-site) to give the 5'-phosphate and 3'-hydroxyl group. It has long been known that AP-sites have mutagenic and cytotoxic effects and their accumulation in DNA is a potential hazard to the cell lifecycle. The structural and biochemical studies of APE1 are complicated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The Trp and FAM fluorescence data were recorded to detect the conformational changes of the enzyme and DNA substrate, respectively, that are induced by Mg 2+ binding. The stopped-flow kinetic curve obtained during the interaction of the apo-APE1-F 13 -substrate complex with Mg 2+ ions was characterized by a single increase in the fluorescent signal in the time range 0.5-20.0 s. As shown above, the increase in the Trp fluorescence corresponds to the catalytic reaction. This result indicates that penetration of Mg 2+ ions into the active site of apo-APE1 leads to formation of a catalytically active state of the enzyme without induction of changes in Trp fluorescence.…”
Section: Constantsmentioning
confidence: 80%
See 2 more Smart Citations
“…The Trp and FAM fluorescence data were recorded to detect the conformational changes of the enzyme and DNA substrate, respectively, that are induced by Mg 2+ binding. The stopped-flow kinetic curve obtained during the interaction of the apo-APE1-F 13 -substrate complex with Mg 2+ ions was characterized by a single increase in the fluorescent signal in the time range 0.5-20.0 s. As shown above, the increase in the Trp fluorescence corresponds to the catalytic reaction. This result indicates that penetration of Mg 2+ ions into the active site of apo-APE1 leads to formation of a catalytically active state of the enzyme without induction of changes in Trp fluorescence.…”
Section: Constantsmentioning
confidence: 80%
“…10 It is known that the level of enzymatic activity of AP-endonuclease APE1 has a considerable influence on the process of the removal of DNA lesions. [11][12][13] Three-dimensional structures of free APE1 [14][15][16] and its covalent complexes with DNA [17][18][19] have been determined by X-ray crystallography. The crystal structures show that APE1 binds to both major and minor grooves of DNA and flips out the abasic deoxyribose phosphate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3−6 A PGO can efficiently hybridize with single-stranded DNA, does not perturb the B-form DNA duplex structure significantly, and is resistant to the action of some nucleases. 5,7,8 It has been shown that an increasing number of modifications in PGO/DNA duplexes significantly attenuates the dependence of melting temperature on solution ionic strength. 6,9 These properties make DMI-containing oligonucleotides a promising tool for biological studies and for accomplishing a wide range of practical tasks such as biosensing, molecular diagnostics, and therapeutics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This modification can be introduced into a desired position of an oligonucleotide during the automatic synthesis using standard phosphoramidite chemistry. The modification makes the phosphodiester group electroneutral and can be combined with various nucleic acid modifications, e.g., phosphothioate, locked nucleic acids (LNAs), or 2′- O -methylated oligoribonucleotides. A PGO can efficiently hybridize with single-stranded DNA, does not perturb the B-form DNA duplex structure significantly, and is resistant to the action of some nucleases. ,, It has been shown that an increasing number of modifications in PGO/DNA duplexes significantly attenuates the dependence of melting temperature on solution ionic strength. , These properties make DMI-containing oligonucleotides a promising tool for biological studies and for accomplishing a wide range of practical tasks such as biosensing, molecular diagnostics, and therapeutics. ,,, Nonetheless, the use of PGOs will become effective when physicochemical and biological properties of these derivatives are well understood. The structures of phosphoryl guanidine (PG)-modified oligomers and their complexes as well as the hybridization propertiessome of the important characteristics for practical applicationshave not yet been studied in detail.…”
Section: Introductionmentioning
confidence: 99%